The Influence of Brand Personality, Service Quality, and Store Atmosphere toward Repurchase Intention Ethic Barbershop Padang - Diza Rahmah Pratiwi; Yunia Wardi (Universitas Negeri Padang, 2019)
AbstractPurpose - This research aims to analyze: (1) The Influence of brand personality toward repurchase purchase intention on customers of Ethic Barbershop (2) The influence of service quality toward repurchase intention on customers of Ethic Barbershop (3) The Influence of store atmosphere toward repurchase intention on customers of Ethic BarbershopMethodology - This type of research is causative research. The population in this study were all men in Padang city who had used Ethnic Barbershop services with a total sample of 151 people taken using purposive sampling because of the unknown population.Finding - Regarding the causal model proposed, the data confirm the relationship set out in the hypothesis. It can therefore be stated that (1) Brand personality has a positive effect and significant to repurchase intention (2) Service quality has a positive effect and significant to repurchase intention and (3) Store Atmosphere has a positive effect and significant to repurchase intentionConclusion - This analysis highlights the positive influences that take part in the brand personality, service quality, and store atmosphere towards repurchase intentions. This is clearly showing in this relationship from an empirical point of view.Limitation - This research only limit with some variables Keywords: Brand Personality, Service Quality, Store Atmosphere, Repurchase Intention